2002
DOI: 10.1002/pola.10323
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of comb‐branched polyacrylamide with cationic poly[(2‐dimethylamino)ethyl methacrylate dimethylsulfate] quat

Abstract: Comb‐branched polyelectrolytes with polyacrylamide backbones and poly[(2‐dimethylamino)ethyl methacrylate methylsulfate] (polyDMAEMA‐DMS) side chains were prepared by free‐radical macromonomer polymerization. PolyDMAEMA‐DMS macromonomers bearing terminal styrenic moieties were synthesized by living anionic polymerization with lithium 4‐vinylbenzylamide (LiVBA) and lithium N‐isopropyl‐4‐vinylbenzylamide (LiPVBA) as initiators. In the presence of LiCl, LiPVBA initiated a living polymerization of 2‐(dimethylamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Unfortunately, ATRP requires great quantities of metal (0.1 to 1 mol‐% with respect to monomer) and catalysts are difficult to remove from the polymer. Nagazaki et al23,24 prepared styrene terminated poly[2‐(diethylamino)ethyl methacrylate] by means of anionic polymerization 13. However, this polymerization technique needs very pure reactants. Faquan Zeng et al25 prepared macromonomers using cationic polymerization of 2‐(diethylamino)ethyl methacrylate starting from lithium 4‐vinylbenzylamide. Wohlrab et al10 used the nitroxyl‐mediated polymerization with hydroxyl terminated initiators that they converted to the vinylpyridine group in a last step.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, ATRP requires great quantities of metal (0.1 to 1 mol‐% with respect to monomer) and catalysts are difficult to remove from the polymer. Nagazaki et al23,24 prepared styrene terminated poly[2‐(diethylamino)ethyl methacrylate] by means of anionic polymerization 13. However, this polymerization technique needs very pure reactants. Faquan Zeng et al25 prepared macromonomers using cationic polymerization of 2‐(diethylamino)ethyl methacrylate starting from lithium 4‐vinylbenzylamide. Wohlrab et al10 used the nitroxyl‐mediated polymerization with hydroxyl terminated initiators that they converted to the vinylpyridine group in a last step.…”
Section: Introductionmentioning
confidence: 99%
“…Ray et al15 simulated a nitroxide‐mediated copolymerization process in a semi‐batch reactor with a constant comonomer feeding rate, and found that composition drifting could be relieved to some degree. Zhu et al16 used a constant comonomer feeding rate to prepare uniform comb‐structured copolymers of acrylamide with polydimethylaminoethyl methacrylate macromonomer.…”
Section: Introductionmentioning
confidence: 99%
“…. Faquan Zeng et al [25] prepared macromonomers using cationic polymerization of 2-(diethylamino)ethyl methacrylate starting from lithium 4-vinylbenzylamide. .…”
Section: Introductionmentioning
confidence: 99%